Colonialismo y orden regional en el mundo árabe - Marzuca Butto, Ricardo (Revista de Estudios Árabes, 2014)
This paper approaches a historical analysis that does not try to be exhaustive, but rather, to favour those significant variables in the evolution of the Near East, from the period that continues at the end of the First World war up to the crisis of 1973 and its major consequences. The European colonialism, its prolongation across the policy of mandates, the penetration of the oil companies and the irruption of the Zionist movement in Palestine, articulate a colonial process up to the end of the second world war, that since 1948, acquires new characteristics and dimensions. That’s why the analysis of the 1956, 1967 and 1973 crises, that in the context of the evolution of the Arab World in the Mashriq region, emphasizes the attempts for constructing an own route of development, its internal contradictions, the main events in the evolution of Iraq, the ascension of The United States in the control of the Middle East and Israel’s expansion in his consolidation as a hegemonic power in the region.